Low Accounting Literacy Hinders Accurate Financial Reporting: Findings from a Study of MSMEs in Bungo Regency - Novita Eka Paradina; Isamuddin (ISTIKHLAF: Jurnal Ekonomi, Perbankan dan Manajemen Syariah, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play a strategic role in both national and regional economic growth. In Bungo Regency, the MSME sector not only contributes to increasing regional income but also creates job opportunities for the local community. However, despite their significant contribution, MSMEs still face various challenges in business management, particularly in terms of systematic and transparent financial reporting. Many MSME struggle to prepare accurate and timely financial reports. One of the main reasons behind this issue is the low level of accounting literacy. A lack of understanding of basic accounting concepts leads to unsystematic transaction recording, which in turn affects the accuracy of financial reports. This study aims to determine the effect of accounting literacy on the preparation of financial reports among Micro, Small, and Medium Enterprises (MSMEs) in Bungo Regency. The sample size used in this study consists of 92 MSME in Bungo Regency. The research method is quantitative, using a descriptive and verificative approach. Samples were selected through purposive sampling of MSME who prepare their own financial reports. The results of the study show that there is a positive and significant influence between accounting literacy and the quality of financial reporting. This indicates that the higher the accounting literacy of MSME actors, the better the quality of the financial reports produced.